2020
DOI: 10.47103/bilturk.675714
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Olive Oil Exports on Economic Growth: Empirical Analysis from Tunisia

Abstract: The contribution of this paper is investigating the influence of olive oil exports on Tunisian economic growth since it's never been treated before. With a view to fulfill this aim, annual data were compiled from the reports of Tunisian Central Bank for the periods between 1970 and 2016, was put to the proof by using Co integration analysis of Error Correction Model. According to the results of the analysis, olive oil exports have a positive impact of economic growth in the long run and in the short run. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 30 publications
5
21
0
Order By: Relevance
“…The finding revealed for Sri Lanka supports the export-led growth hypothesis in the short-run. Similar short-run findings for the case of citrus export were revealed by Bakari (2018) in Tunisia. The outcome suggests that a structured frame of action and long-term policy implications can drive Sri Lanka's tea export to the long-run economic growth.…”
Section: Nexus Between Tea Export and Economic Growthsupporting
confidence: 81%
“…The finding revealed for Sri Lanka supports the export-led growth hypothesis in the short-run. Similar short-run findings for the case of citrus export were revealed by Bakari (2018) in Tunisia. The outcome suggests that a structured frame of action and long-term policy implications can drive Sri Lanka's tea export to the long-run economic growth.…”
Section: Nexus Between Tea Export and Economic Growthsupporting
confidence: 81%
“…Studies have been presented that investigate factors that influence agricultural exports (Abolagba, Onyekwere, Agbonkpolor, & Umar, 2010;Boansi, 2013). Various studies also explore the impact of agriculture exports on economic growth in various economies, such as South Africa (Bulagi, Hlongwane, & Belete, 2015), Tunisia (Bakari, 2017a(Bakari, , 2017b, Southeastern European countries (Bakari & Mabrouki, 2017), Nigeria (Ijirshar, 2015;Verter & Bečvářová, 2016), and India (Ohlan, 2013). Moreover, similar results were also noted by Sanjuán-López & Dawson (2010) for 42 developing countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Interestingly Bakari (2018) investigated the relation between citrus export and Tunisian economic growth. The author found that the share of citrus in total exports fluctuated in different years, but its contribution was crucial.…”
Section: Review Of Literaturementioning
confidence: 99%